Folic Acid Attenuates N-Methyl-N’-Nitro-N-NitrosoguanidineInduced Gastric Mucosal Injury in Rats - , Caiting Peng, Li Wang, Yuan Liang, Li Che, Rongjing Sun, Jia Yu, Jiamin Gong, Dandan Wang, Suizhi Cheng, Qingqing Yang, Tao Jing, Zhenzhong Liu (Turkish Journal of Gastroenterology 1, 2024)
Background/Aims: N-Methyl-N’-nitroso-N-nitrosoguanidine (MNNG) is suspected to increase the risk of developing stomach cancer. Folic acid (FA) is familiar with decreasing inflammation. We expected that FA would protect against MNNG-induced gastric mucosal injury.Materials and Methods: Thirty 12-week-old SPF-grade female Sprague-Dawley (SD) rats were treated with MNNG and given different dosages of FA as an intervention measure. Quantitative polymerase chain reaction (qPCR) was used to analyze the expression of IL-1, IL-6, IL-8, IL-18, TNF-α, NLRP3, ASC, and caspase-1 genes. The enzyme-linked immunosorbent assay (ELISA) was utilized for the identification of inflammatory cytokines. Western blot was accustomed to detecting IL-1β, IL-18, and NLRP3 inflammatory vesicles in gastric tissue. Furthermore, the gastric mucosal tissues underwent histological examination.Results: Our investigation demonstrated that FA reduced MNNG-induced inflammatory factor increase by decreasing NF-κB signaling (P < .05). Furthermore, FA prevented the MNNG-induced upregulation of NLRP3 inflammasome-related genes and proteins (all P < .01).Conclusion: Our data imply that MNNG exposure stimulates the NF-κB/NLRP3 pathway, while FA suppresses it, limiting stomach mucosal inflammation. Cite this article as: Peng C, Wang L, Liang Y, et al. Folic acid attenuates N-methyl-N’-nitro-N-nitrosoguanidine-induced gastric mucosal injury in rats. Turk J Gastroenterol. 2024;35(11):839-848.